The Effect of Principal Supervision on Teacher Performance: Literature Review - Surya Purnama Putra; Hasan Hariri (Penerbit Goodwood, 2023)
Teachers play an important role in learning. As a professional teacher, supervision is needed to improve the implementation of the teaching process. The purpose of this literature review is to examine and analyze the impact of academic supervision on improving teacher performance. The method in this study was carried out by reviewing related articles about academic supervision and teacher performance. The research sample was focused on the Google Scholar search engine with academic guidance and teacher performance as the main research constraints and then identified. The results of the article review show that most of the role of academic supervision is very influential in improving teacher performance. Therefore, effective academic supervision requires the will of the principal to plan, implement and evaluate supervision. Purpose: The purpose of this literature review is to examine and analyze the impact of academic supervision on improving teacher performance. Methodology: The review process begins with a search engine, Google Scholar, to find articles with keywords.